EDUKASI KESEHATAN SALURAN CERNA SEBAGAI UPAYA DALAM MENCEGAH STUNTING PADA SISWA SEKOLAH DASAR NEGERI 11 SANUR - Nursini, Ni Wayan; Lestari, Putu Indah; Dewi, Ni Nyoman Ari Indra; Yogeswara, Ida Bagus Agung (Universitas Mataram, 2024)
Stunting is a condition of stunted physical growth in children due to malnutrition, a serious problem that can have a long-term impact on the health, education and development of school-age children. In addition, the incidence of stunting is also related to the health condition of the gastrointestinal tract, especially the balance of the normal flora population. When a child's digestive tract is healthy and nutrient absorption is maximized, it indirectly reduces the risk of nutritional problems, especially stunting. This PKM activity aims to provide education, training and assistance to teachers, students and parents regarding stunting prevention so that they can contribute to realizing the Golden Generation 2045. Community Development is the method used in PKM, technically the activities are carried out by socialization, education, training, mentoring and monitoring. This PKM activity targets 5th and 6th grade students of SDN 11 Sanur who are early adolescents who need to get education and knowledge related to stunting. Based on the activities that have been carried out, an increase in understanding related to stunting is 76,63%. The increase in understanding related to gastrointestinal health has also increased by 84,09%. This community service program is very beneficial for the partner community and is able to increase the partner community's understanding of things to improve health status in an effort to prevent stunting.